A novel traveling wave fault location method for transmission network based on time linear dependence. (March 2021) - Yu, Kun; Zeng, Jupeng; Zeng, Xiangjun; Liu, Feng; Zu, Yarui; Yu, Quan; Zhuo, Chao
Highlights: A novel transmission shortest path of fault traveling wave algorithm is presented. A novel fault location method based on multi-point linear fitting is proposed. The accurate fault distance can be obtained intuitively in the coordinate plane. The accurate fault location can be realized even with time recording error. Abstract: Transmission network faults may not be located accurately in some abnormal conditions, such as traveling wave location device faults, startup failure and time recording error. In order to improve them, a novel traveling wave fault location method based on time linear dependence is proposed. The proximal point optimization algorithm (PPOA) is used to find the shortest transmission path of fault traveling wave. The linear fitting between the arrival time of the traveling wave head recorded by each substation and the transmission distance is made on the Cartesian coordinate plane, according to the characteristic that the length of the shortest path is directly proportional to the traveling wave transmission time. The information fusion for the traveling wave arrival time at each substation is achieved by linear regression analysis to correct the error information. The accurate fault location is obtained direct by coordinate information of the intersection of the fitted line and the coordinate axis. Finally, the traveling wave location system based on this method has been successfully tested in Hunan Power Grid. PSCAD simulation and field test results prove that the proposed method can effectively reduce the recording error in the arrival time of the fault traveling wave at each substation while improving the reliability and accuracy of fault location.